The return of individual research findings in paediatric genetic research. Issue 3 (8th November 2010) - Hens, Kristien; Nys, Herman; Cassiman, Jean-Jacques; Dierickx, Kris
Abstract : The combination of the issue of return of individual genetic results/incidental findings and paediatric biobanks is not much discussed in ethical literature. The traditional arguments pro and con return of such findings focus on principles such as respect for persons, autonomy and solidarity. Two dimensions have been distilled from the discussion on return of individual results in a genetic research context: the respect for a participant's autonomy and the duty of the researcher. Concepts such as autonomy and solidarity do not fit easily in the discussion when paediatric biobanks are concerned. Although parents may be allowed to enrol children in minimal risk genetic research on stored tissue samples, they should not be given the option to opt out of receiving important health information. Also, children have a right to an open future: parents do not have the right to access any genetic data that a biobank holds on their children. In this respect, the guidelines on genetic testing of minors are applicable. With regard to the duty of the researcher the question of whether researchers have a more stringent duty to return important health information when their research subjects are children is more difficult to answer. A researcher's primary duty is to perform useful research, a policy to return individual results must not hamper this task. The fact that vulnerable children are concerned, is an additional factor that should be considered when a policy of returning results is laid down for a specific collection or research project.